Rumah tiang dua belas Kelantan: satu kajian ruang rumah tradisional Melayu - Nor Hafiza Othman (2014)
The cofounding plan in traditional Malay houses is becoming severe with the decreasing interests in sustaining cultural values. With the trending construction interests focusing more in revenues, the relationship between the ecosystem and heritage will lose its balance reflecting in the equanimity of a house built. Subsequently, this may affect the existence of the traditional Kelantanese house with its conventional construction values. Capturing the inhabitants’ requisites the layout of traditional Malay houses would also integrate the space design with the influences of religious values and harmony with the environment. Unfortunately, there are not many people who are knowledgeable in the space design of traditional Malay houses with the trending change and this is especially true for the infamous Kelantanese Twelve-Pillar House. The present study investigates the space design of traditional Malay houses giving focus to the design layout of the Kelantanese Twelve-Pillar House. The study utilizes two sets of measured drawings which involved the study on Nik Fatimah Twelve-Pillar House and the Wan Mek House obtained from the Centre for the Study of the Built Environment Malay World (KALAM) at UniversitiTeknologi Malaysia (UTM). The methodology of the study was conducted through content analysis. The data analysis takes on the qualitative measures of visual descriptive analysis, exploration and interpretations of data through the assembled drawings and specifications